Reorientasi Peranan Pesantren Pada Era Pembangunan Menuju Partisipasi Pemberdayaan Masyarakat Bawah - Taufik Nugroho (Universitas Cokroaminoto Yogyakarta, 2017)
It goes without saying that Pesantren has been a site of great potential to continue its role playing more broadly, not only as confine as to become a guardian of social piety and the center for the spreading of Islam in the countryside, but also playing its role as a counter part for the development of the Indonesian government. The expansion is on the aspect of political policies, empowerment of the people's economy as well as character education .